A Study on Work Life Balance of it Enabled Bpo Workers in Bangalore City (Karnataka) - M. Chockalingam, S; Sudarshan, P (International Journal of Engineering and Technology, 2018)
Human beings in this earth have to work for inevitable reasons. For the purpose of employment people even migrate to their nearest cities or even they may relocate themselves too far off places, due to swiftly growing population across the country and also numbers of people getting qualified degrees have increased a lot. On the other hand scope for employment is considerably reducing day by day. This has made job markets completely employee driven. When job markets become employee driven, by all means employees will extract much work from employees. This will make them spend more and more time at the workplace and less time with their families. The result of this will lead to imbalance between work and family life. This study tries to cover many insights on work life balance especially covering major BPO employees working at Bangalore.Â Â